Religiosity and Personal Beliefs Regarding Abortion: Results from a Survey of Social Work Students in the United States. Issue 2 (3rd April 2018) - Bird, Melissa; Begun, Stephanie; McKay, Kimberly
Abstract: Religiosity is typically one of the most relevant predictors of abortion attitudes. Social workers and the clients they serve represent diverse identities and beliefs, and social workers play a critical role in helping clients to obtain information and resources and to make important life decisions, including ones pertaining to abortion. Survey data were collected from 504 social work students, who were asked about their practice and education experiences and their personally held beliefs about abortion. Linear regressions showed that higher religiosity was significantly associated with greater endorsement of anti-abortion attitudes. Social work, as a profession, should further emphasize training, education, and research regarding abortion to prepare students better to facilitate clients' self-determined decision-making regarding abortion regardless of social workers' personal religious and abortion beliefs.